2019
DOI: 10.3390/molecules24061179
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Liver Targeting of Camptothecin via Conjugation with Deoxycholic Acid

Abstract: Camptothecin (CPT) shows potent anticancer activity through inhibition of topoisomerase I. However, its water insolubility and severe toxicity limit its clinical application. Coupling with bile acid moieties is a promising method for liver-targeted drug delivery, which takes advantage of the bile acid receptors on hepatocytes. In this study, we evaluated the potential liver targeting and stability of a deoxycholic acid-CPT conjugate (G2). The competitive inhibition of antitumor activity experiment based on bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…39) The extent of biliary excretion of a compound may be affected by many physicochemical factors, such as molecular weight, polarity, sex, chemical structure and metab-olism. 40) Furthermore, the extent of some compounds varies widely with species. It has been reported the threshold molecular-weight for humans is approximately 500-600, while 325 is the minimum molecular-weight for the rat.…”
Section: Characterization Of G2mentioning
confidence: 99%
“…39) The extent of biliary excretion of a compound may be affected by many physicochemical factors, such as molecular weight, polarity, sex, chemical structure and metab-olism. 40) Furthermore, the extent of some compounds varies widely with species. It has been reported the threshold molecular-weight for humans is approximately 500-600, while 325 is the minimum molecular-weight for the rat.…”
Section: Characterization Of G2mentioning
confidence: 99%
“…Recently dihydroartemisinin–UDCA derivatives were reported to improve the cytotoxicity of dihydroartemisinin towards leukemia cells [ 90 ] and hepatocellular carcinoma [ 91 ]. A deoxycholic acid-Camptothecin conjugate [ 92 ] was recently proved by Xiao et al to enhance the targeted delivery of anticancer molecules in liver by exploiting the specific BA-BA receptors interaction. A series of nucleoside [ 93 ] and platinum(II) [ 94 ]-BADs were screened to test the cytotoxic activity in different tumor cell lines.…”
Section: Functionalized Bas In Medicinementioning
confidence: 99%
“…Better inhibition, enhanced stability. [35,36] The anticancer profiles of bile acid-nucleoside hybrids were reported in the last decade. The 1,2,3-triazole scaffold was chosen to connect bile acids to deoxyadenosine-nucleoside analogues via click chemistry and the corresponding hybrids were evaluated for their cytotoxicity against a panel of four different human cancer cell lines and normal fibroblast cells (Scheme 1) [28].…”
Section: Bile Acid Hybrid Molecules Based On Natural Bioactive Moleculesmentioning
confidence: 99%
“…Stability studies in blood rat serum of hybrid 45 showed that conjugation actually stabilizes CPT, resulting in an increase of hybrid half-life to up to 24 h, compared to a 2.3-h half-life of CPT alone. More recently, the same authors demonstrated in vitro and in vivo that DC-CPT hybrid 46 was more stable than CTP alone, and that its potential to target liver was remarkably enhanced by deoxycholic bile acid conjugation [36].…”
Section: Bile Acid Hybrid Molecules Based On Natural Bioactive Moleculesmentioning
confidence: 99%